As negociações para o fim do apartheid características e estratégias na mesa de negociação - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The goal of this monograph is to analyse the main steps of the negotiation process that happened in South Africa between 1985 and 1993. This negotiation process aimed to support the transition from apartheid to democracy in South Africa. Firstly, the secret bilateral negotiations between the main oppositional party to the south african government, the African National Congress, and the party wich held the power at the time, the National Party, will be analysed. Those negotiations lasted approximately 5 years, from 1985 to 1990. Furthermore, the formal negotiations, that went from 1990 to 1993, and culminated in the democratic elections of 1994, will also be analysed. The main steps of such negotiations will be analysed, as well as the international, regional and internal conjuncture, that were the background for the process, and had a big influence in the denouement of the process. For such purpose, several books refering to the transition from a segregationist regime to a democratic regime in South Africa, as well as official documents of the period, were studied. In this monograph’s analysis, it is intended to understand wich were the factors that contributed to the sucessful end of the negotiation process.
Keywords: International relations; Apartheid; South Africa; CNPQ::CIENCIAS HUMANAS; Relações internacionais; Segregação racial; África do Sul